Analisa Laju Infiltrasi Daerah Riparian Pada Sungai Pappa’ - kasmawati kasmawati; Farida G; Marupah Marupah; indriyanti indriyanti (Universitas Muslim Indonesia, 2023)
Infiltration is a very important component because the problem of soil conservation is the regulation of the relationship between rainfall intensity and infiltration capacity, as well as the regulation of surface runoff. Surface runoff can only be regulated by increasing the ability of the soil to store water, mainly by improving or increasing infiltration capacity. Infiltration capacity is the maximum rate of water that can enter the soil at one time. Infiltration is one of the phases of the hydrological cycle, it is important to know because it will affect runoff, flooding, erosion, availability of water for plants, groundwater, and availability of river flow in the dry season. So this study analyzed how infiltration affects the slope and compared using Horton's formula. In this study, data collection methods were carried out in the laboratory and then processed using the Horton method and the results were compared. From the research, it was found that a large infiltration rate with a small slope besides that, with direct observation the infiltration rate is greater than the Horton method.